2019
DOI: 10.1111/jce.14160
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent atrial fibrillation/flutter detection after ablation or cardioversion using the AliveCor KardiaMobile device: iHEART results

Abstract: Objective: This study evaluated the impact of daily ECG self-recordings on time to documented recurrent atrial fibrillation (AF) or atrial flutter (AFL) and time to treatment of recurrent arrhythmia in patients undergoing catheter radiofrequency ablation (RFA) or direct current cardioversion (DCCV) for AF/AFL. Background: AF recurrence rates after RFA and DCCV are 20–45% and 60–80% respectively. Randomized trials comparing mobile ECG devices to standard of care have not been performed in an AF/AFL population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Kaura et al [ 34 ] reported a dropout of 22.4% and did not address this data in the report. This was also true for the RCT by Goldenthal et al [ 32 ], but the dropout in this trial was just 2.1%. As for allocation concealment in the trial carried out by Halcox et al [ 29 ], no clarity was provided in the method section of the paper.…”
Section: Resultssupporting
confidence: 70%
“…Kaura et al [ 34 ] reported a dropout of 22.4% and did not address this data in the report. This was also true for the RCT by Goldenthal et al [ 32 ], but the dropout in this trial was just 2.1%. As for allocation concealment in the trial carried out by Halcox et al [ 29 ], no clarity was provided in the method section of the paper.…”
Section: Resultssupporting
confidence: 70%
“…In the iHEART study, use of a mobile ECG device paired with a smartphone increased the detection of recurrent atrial arrhythmias after atrial fibrillation ablation, which strongly predicted later arrhythmia recurrence with a trend towards lower hospitalization and ER visits. 18 The randomized Heartline study (ClinicalTrials.gov Identifier: NCT04276441) is currently underway to determine if use of a 1-lead ECG capable smartwatch can not only increase the diagnosis of J o u r n a l P r e -p r o o f atrial fibrillation, but also improve major cardiovascular outcomes of stroke, myocardial infarction and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that AF recurrence after ablation may be asymptomatic. Studies have shown that asymptomatic AF may be increasingly common after ablation and potentially pose a greater thromboembolic risk than symptomatic AF [17][18][19] . In the present study, we found that 785/3299 (23.8%) of AF detected after ablation were asymptomatic, that may explain the poor compliance with anticoagulation after catheter ablation even if patients receive recommendations of anticoagulation from doctors.…”
Section: Discussionmentioning
confidence: 99%